Coronary Endothelial Dysfunction in Women with Type 2 Diabetes Measured by Coronary Phase Contrast Flow Velocity Magnetic Resonance Imaging. Issue 7 (October 2015) - Maroules, Christopher D.; Chang, Alice Y.; Kotys-Traughber, Melanie S.; Peshock, Ronald M.
Objective: The aim of this study was to determine if differences in coronary endothelial function are observed between asymptomatic women with type 2 diabetes mellitus (DM) and control subjects using coronary phase contrast flow velocity magnetic resonance imaging in response to cold pressor stress, an established endothelium-dependent vasodilatory stress. Methods: Phase contrast flow velocity imaging of the right coronary artery was performed in 7 asymptomatic premenopausal women with DM and 8 healthy female participants in response to the cold pressor test at 3 T. Results: There was no significant difference in percent increase in coronary flow velocity from rest to peak flow velocity between DM and control subjects (32% ± 22% vs 46% ± 17%; P = 0.11). However, percent increase in coronary flow velocity was lower in DM than in control subjects (−3% ± 14% vs 31% ± 30%; P = 0.01) during the second minute of cold pressor stress, when endothelial-mediated vasodilation should occur. Conclusions: Asymptomatic women with DM demonstrate reduced coronary flow velocity during the second minute of cold pressor stress, indicating coronary endothelial dysfunction.